Depiction of Hari-Hara Hiranyagarbha - Temples of India Project Team (Jio Institute, 2024)
The rear wall of the garbhagriha has a projection depicting a syncretic image. This image depicts Surya, Vishnu and Shiva coming together to form a deity called Hari-Hara Hiranyagarbha. The deity is depicted with three heads and six arms, standing alongside his attendants Dandaka and Pingala. Adorned with a beautiful crown and jewellery, the deity is wearing knee-length boots, which confirms that the frontal face and body represent Surya, who is shown holding flowers in both his hands. While in his upper hands, one can notice sarpa (snakes) which is an attribute of Shiva, and the lower arms grasp a shankha (conch shell) and chakra (discus), symbols associated with Vishnu.